REFRAMING CUSTOMARY INSTITUTIONS AS SOCIO-CULTURAL CAPITAL IN FAMILY EDUCATION: EVIDENCE FROM AN INDIGENOUS COMMUNITY IN INDONESIA - Ewi Darman Ndraha; Serafin Wisni Septiarti; Fauzi Kurniawan; Ratna Natalia Mendrofa; Arsen Lawolo; Viqri Rolanda (PEDAGOGIK : JURNAL PENDIDIKAN, 2026)
Customary institutions remain an important part of social life in many indigenous communities, yet studies examining their role as socio-cultural capital in strengthening family education are still limited. This study aims to analyze the role of customary institutions in reinforcing family education. The research employed a qualitative case study approach using in-depth interviews, observation, and documentation. Informants consisted of customary leaders, married couples, and community members selected purposively. The findings reveal that customary institutions contribute significantly to family strengthening through various traditional mechanisms, including Falöwa as a medium for reinforcing kinship relations, Famotu Ono Nihalö as premarital guidance for women, Fanika Era-Era Mböwö as moral education for men, and Amatunowa as a customary forum for family conflict resolution. These practices transmit values of responsibility, respect, solidarity, cooperation, and social harmony across generations. This study concludes that customary institutions function not only as cultural heritage but also as socio-cultural capital that enhances family resilience and maintains social cohesion within indigenous communities.